Parasitismo de Gronotoma melanagromyzae Baerdsley (Hymenoptera: Figitidae: Eucoilinae), en el arrocillo del tomate de cáscara, Melanagromyza tomaterae Steyskal (Diptera: Agromyzidae) - Palacios Torres, Rogelio Enriquez; Bautista Martínez, Néstor (Instituto de Ecología, A.C., 2020)
Melanagromyza tomaterae Steyskal is registered as a new host for Gronotoma melanagromyzae Beardsley, collected in the Valley of Mexico, Chapingo, Mexico.